Electromagnetism for engineers - Hammond, P. (Oxford University Press, 1997)
This is a fully revised and updated edition of a widely used introductory textbook on electromagnetism. It covers all the fundamental aspects of this important topic in electrical engineering. The approach is eminently practical and requires little mathematics other than elementary differentiation, integration, and trigonometry. It will continue to appeal to students studying this conceptually challenging but fundamental subject. New sections on electromechanics (conversion of electric and magnetic energy in mechanical energy and vice versa) and high-frequency phenomena (transmission lines, waveguides, optical fibres, and radio propagation) enhance the usefulness of the book